The Mathematics Teaching Development through Teaching-learning Enjoyment in Geometric Analysis - PHOMMANITH, Khamsone; VATHANAVONG, Thongthiane; VONGSIPHASEUTH, Bounmor; SYHALATH, Soulagon (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
The purposes of this study were to 1) develop and improve a teaching model for learning and enjoying in Mathematics (Geometric Analysis), 2) to find students’ the achievement, and 3) to learn students’ attitude toward mathematics (Geometric Analysis). The target groups consisted of 35 third year students who are studying mathematics in the second semester, academic year 2017- 2018 at Department of Mathematics, Faculty of Education. The instruments were lesson plan, achievement test, attitude test, and focus group. Data was analyzed by t-test, mean, standard deviation, and content analysis. The results of this study were shown as follows that the Model for learning and enjoying in Mathematics (Geometric Analysis) consisted of 5 steps; Teach, Team, Tournament, Test, and to build confidence, are called the “5T Model”. After using the 5T Model, the subjects had significantly achieved in learning mathematics (higher than 75%), and they got high level scores in attitude towards mathematics (Geometric Analysis). For improvement of the 5T Model, it was found that in the step of “Tournament” could be enhanced if participants are allowed to use paper to write the answer simultaneously. Through observation of the teaching process of 5T Model appeared to reduce the difference in gender and abilities of learners. In the step of, “To build confidence” the model can help students to be more confident increase lessons’ understanding because they had opportunity to review the lessons